Very high-resolution 1H MAS NMR of a natural polymeric material (Solid State Nuclear Magnetic Resonance, 1999)
The use of ultrafast magic angle spinning (>30 kHz) in tandem with delayed echo acquisition is shown to yield very high-resolution 1H MAS NMR spectra of complex natural organic materials. For the first time, very high-resolution 1H MAS NMR spectra are reported for cork and wood components, two natural materials with great economic importance. The effect of the spinning rate on the 1H NMR spectra was evaluated with single-pulse acquisition and delayed-echo acquisition. The delayed-echo acquisition spectra presented linewidths as sharp as 67 and 25 Hz. The narrow peaks, characterised by proton spin–spin and spin–lattice relaxation, were assigned to the isotropic chemical shifts and the general spectral features were shown to correlate with the sample chemical structure. The tentative assignments of cork 1H MAS NMR signals were presented.